2021
DOI: 10.3389/fmed.2021.744512
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Increases the Risk of Hepatocellular Carcinoma After Direct-Acting Antiviral Therapy: Systematic Review and Meta-Analysis

Abstract: Background: Hepatitis C virus (HCV)-infected patients treated with direct-acting antivirals (DAAs) are still at risk of developing hepatocellular carcinoma (HCC) after sustained virologic response (SVR). This study aimed to investigate the role of diabetes mellitus (DM) as a potential predictive risk factor in developing de novo HCC in HCV-infected patients after DAA treatment.Methods: This study was registered on PROSPERO under registration number CRD42021230457. We performed a systematic search in four medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“… 20 , 21 , 22 According to the recent meta‐analysis conducted by Vancsa et al ., DM increases the risk of HCC development after SVR following DAA treatment of HCV patients. 6 In this manuscript, Vancsa et al . concluded that there is a two‐way association between HCV infection and DM.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 20 , 21 , 22 According to the recent meta‐analysis conducted by Vancsa et al ., DM increases the risk of HCC development after SVR following DAA treatment of HCV patients. 6 In this manuscript, Vancsa et al . concluded that there is a two‐way association between HCV infection and DM.…”
Section: Discussionmentioning
confidence: 92%
“…The risk of de novo hepatocellular carcinoma (HCC) in patients who achieve a sustained virologic response (SVR), through treatment with interferon or DAA, is known to be reduced. 3 , 4 , 5 , 6 Extrahepatic manifestations such as cryoglobulinemic vasculitis, lymphoma, cardiovascular diseases, and diabetes mellitus (DM) are recognized as a feature of HCV infection and can influence the morbidity, quality of life, and mortality of these patients. Several studies have shown a close link between viral eradication and a lower risk of extrahepatic manifestations, as well as an improvement of existing extrahepatic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The 53 patients with a history of HCC were significantly older (75.6 years vs 66.5 years; P < 0.01) than the 258 patients with no history of HCC. The rates of diabetes, a risk factor for HCC after DAA treatment[ 20 ] (35.8% vs 3.1%; P < 0.01) and liver cirrhosis (34.0% vs 20.2%; P < 0.01) were significantly higher, whereas the rates of HCV genotype 2 (13.2% vs 25.6%; P = 0.04) were significantly lower, in patients with than without a history of HCC. In addition, serum albumin concentrations (3.5 g/dL vs 4.0 g/dL; P < 0.01) and platelet counts (12.9 × 10 4 /mL vs 16.7 × 10 4 /mL; P < 0.01) were significantly lower, whereas Fib-4 index (6.27 vs 3.37; P < 0.01) and AFP concentrations (23.7 ng/mL vs 9.4 ng/mL; P = 0.047) were significantly higher in patients who had a previous history of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…(8) Independent of the presence of cirrhosis or the cause of the underlying liver disease, patients with diabetes have a 2-to 3-fold higher risk of developing HCC than individuals without diabetes. (9)(10)(11)(12)(13)(14)(15)(16)(17) A longer duration of diabetes may also be associated with an incremental increase in the risk of HCC, (18)(19)(20) and diabetes is an independent risk factor associated with reduced overall survival and disease-free survival in patients with HCC. (14,21,22) In addition, the proportion of diabetes among patients with HCC of nonviral etiology has continued to increase considerably during the last two decades.…”
Section: Introductionmentioning
confidence: 99%